Take cover: Incentivising wider social insurance participation in South Africa - Borros, Georgina (School of Economics, 2022)
This paper examines the gap in social insurance coverage in semi-formal enterprises, and explores options for incentivising participation by lower income workers in a comprehensive statutory social security scheme. A probit model is used to quantify current patterns of UIF and pension coverage. The analysis confirms that business owners, employees in the informal sector and those without an employment contract are significantly less likely to participate. A transition matrix is used to assess the trends in participation over the 2020 lockdown period - showing a statistically significant increase in pension fund and UIF participation, which suggests that the Covid-19 TERS benefit generated an availability heuristic effect. Two subsidy models are examined, designed to incentivise wider participation: the first being a subsidy for comprehensive social insurance cover (including pension and unemployment insurance) and the second a subsidisation of unemployment insurance only. Both subsidy models are costed. In the event of full participation, the unemployment insurance subsidy would cost the state R16 billion annually, while a comprehensive social insurance subsidy would amount to R48 billion annually. The unemployment insurance subsidy is advised as an immediate avenue for action, while the comprehensive plan remains a goal for higher welfare in the long run.